2022
DOI: 10.1007/s00366-022-01654-1
|View full text |Cite
|
Sign up to set email alerts
|

A 3D multi-agent-based model for lumen morphogenesis: the role of the biophysical properties of the extracellular matrix

Abstract: The correct function of many organs depends on proper lumen morphogenesis, which requires the orchestration of both biological and mechanical aspects. However, how these factors coordinate is not yet fully understood. Here, we focus on the development of a mechanistic model for computationally simulating lumen morphogenesis. In particular, we consider the hydrostatic pressure generated by the cells’ fluid secretion as the driving force and the density of the extracellular matrix as regulators of the process. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…Although matrix stiffness-regulated differences in lumenogenesis by hPSCs have not been established in prior studies, other lumen forming cell types are shown to exhibit ECM stiffness-regulated lumenogenesis in computational and experiment models. Camacho-Gómez et al built a model to simulate lumenogenesis, predicting that stiffer matrices would resist the hydrostatic pressure from fluid intake that drives lumen expansion, leading to multilayer aggregates with smaller lumens . Findings by Enemchukwu et al also emphasized that lumen formation in MDCK cells is restricted to a narrow range of optimum ECM elasticity, while abnormal morphogenesis is observed at higher or lower elastic moduli .…”
Section: Discussionmentioning
confidence: 99%
“…Although matrix stiffness-regulated differences in lumenogenesis by hPSCs have not been established in prior studies, other lumen forming cell types are shown to exhibit ECM stiffness-regulated lumenogenesis in computational and experiment models. Camacho-Gómez et al built a model to simulate lumenogenesis, predicting that stiffer matrices would resist the hydrostatic pressure from fluid intake that drives lumen expansion, leading to multilayer aggregates with smaller lumens . Findings by Enemchukwu et al also emphasized that lumen formation in MDCK cells is restricted to a narrow range of optimum ECM elasticity, while abnormal morphogenesis is observed at higher or lower elastic moduli .…”
Section: Discussionmentioning
confidence: 99%
“…In the context of mathematical modeling, signals are inputs to constitutive laws or agent rules. We broadly surveyed mathematical and biological models from cancer biology 41,63,[104][105][106][107][108][109][110][111][112][113] , tissue morphogenesis 104,[114][115][116][117][118] , immunology 41,[99][100][101]119,120 , and microbial ecosystems 121,122 , to generalize classes of inputs to cell behavioral rules, generally including chemical factors, mechanical cues, cell volume (e.g., for volume-based cycle checkpoints), physical contact with cells, live/dead status, current simulation time (for use in triggering events), and accumulated damage (e.g., from effector attack [123][124][125] ). The signals are summarized in Table 2.…”
Section: Signalsmentioning
confidence: 99%
“…For example, Ref. [143] applies the agent-based model approach in which each cell is assumed to be a single non-deformable sphere.] For examples, an earlier review article [24] explained the Brodland's finite element model, in which a single cell in an epithelial monolayer is divided into a few discrete finite elements [144,145], the immersed boundary model (IBM), in which the dynamics of cell boundaries is immersed in the surrounding fluid mimicking cytoplasm and extracellular matrix [146][147][148][149][150][151], and the subcellular element model (SEM), which represents the cell body by the meshwork of discrete elements each of which have viscoelastic properties [152,153], etc.…”
Section: Experimental Readouts For Comparisonmentioning
confidence: 99%